Identificação e análise de parâmetros de motores de corrente contínua sem escovas - Bastos, Fellipe Fonseca; Silva, Monique Fernandes da (IEEE Latin America Transactions (Volume: 14, Issue: 7, July 2016), 2016)
This paper presents the parameters identification and analysis of brushless direct current motors. As it is not always possible to find such information in manuals, the objective was to perform experiments to find the parameters of the brushless direct current motors. By the results of the experiments, it was possible to determine important constants for obtaining the motor transfer function, and the efficiency and performance motor curves. The motor transfer function is a mathematical representation to describe the system inputs and outputs, and it is used in response analysis and control simulations. Besides contributing to the procedure to obtaining the transfer function, and efficiency and performance curves for research applications in the control and automation field, this work contributes to the obtained results for the motor A2212/13T.
Parameters identification and analysis of brushless direct current motors
Keywords: ENGENHARIAS::ENGENHARIA DE ENERGIA; Brushless Direct Current Motor; Parameters; Identification; Brushless DC motors; Rotors; Torque; Parameter estimation; Pulse width modulation